Long-Term Physicochemical, Nutrient, and Biological Water Quality Data from Inland Lakes of the Yucatán Peninsula (CONAGUA Monitoring Program, 2012–2020) - Hernández Hernández, Plutarco (PANGAEA, 2026)
This dataset compiles long-term water quality measurements from multiple lacustrine systems in the Yucatán Peninsula collected between 2012 and 2020 as part of the CONAGUA monitoring program. Sampling sites are located across inland lakes within the karstic low-relief landscape of the peninsula, where surface water conditions are strongly linked to the regional aquifer system. The dataset includes physicochemical, nutrient, and biological variables such as chlorophyll-a concentration, fecal and total coliform bacteria, biochemical oxygen demand, total nitrogen and total phosphorus concentrations, total dissolved solids, electrical conductivity, pH, dissolved oxygen concentration, total suspended solids, turbidity, and water temperature. Geographic coordinates and sampling year are provided for each record to facilitate temporal and spatial analyses. Additionally, derived indicators such as the Carlson Trophic State Index (TSI) and the Water Quality Index (WQI) are included to assess trophic conditions and overall water quality. This dataset provides an important multi-year baseline for evaluating temporal trends, eutrophication processes, and water quality dynamics in inland aquatic ecosystems of the Yucatán Peninsula.
Keywords: biochemical oxygen demand; chlorophyll-a; Conductivity; Dissolved oxygen; Nitrogen; pH; Phosphate; Temperature; total coliforms; turbidity